Improving access to cancer information and supportive care services: A systematic review of mechanisms applied to link people with cancer to psychosocial supportive care services. Issue 10 (16th June 2021) - White, Victoria M.; Pejoski, Natalie; Vella, Elizabeth; Skaczkowski, Gemma; Ugalde, Anna; Yuen, Eva Y. N.; Livingston, Patricia; Wilson, Carlene
Abstract: Objective: Previous research has described the low uptake of psychosocial support services in people living with cancer. While characteristics of individuals using services have been examined, mechanisms applied to link individuals to support services are less frequently considered. This review aims to identify the mechanisms used to link people with cancer to support services and assess their impact. Methods: Systematic searches of Pubmed, CINAHL, EMBASE and PsycINFO were conducted up to May 2020. Studies reporting service use associated with mechanisms to link adults with cancer to support services targeting emotional, informational, practical or social support needs were eligible. Eligible study designs included controlled trials, pre‐post designs and observational studies. Study quality was assessed and a narrative synthesis of findings undertaken. Results: A total of 10 papers (from 8, 037 unique titles) were eligible. Testing the feasibility of the linkage mechanism was the primary aim in five (50%) studies. Three linkage mechanisms were identified: (a) outreach from the support service; (b) clinician recommendation/referral; (c) mailed invitation. Outreach was the most successful in connecting people with cancer to services (52%–90% use); clinician recommendation/referral was least successful (3%–28%). The impact of different linkage mechanisms for different demographic groups was not assessed. Conclusions: Outreach from services shows the most potential for increasing access to support services. However, the limited number of studies and limitations in the types of support services people with cancer were linked to, demonstrated the need for further work in this area. Identifying mechanisms that are effective for underserved, high‐needs patient groups is also needed.